Assessing the Impact of Storage Conditions on the Chemical and Physical Properties of Powdered Infant Formula (مجلة العلوم الشاملة, 2025)
This research investigated the influence of room-temperature storage of powdered infant formula on the quality of samples obtained from pharmacies in Khums, Libya. Moisture content, pH, electrical conductivity, total dissolved solids (TSS), and vitamin C concentration were the key quality indicators analyzed. Measurements indicate that product quality decreases significantly during the week following package opening. All samples demonstrated significant increases in moisture content, although one sample's initial moisture content was above expected levels. The subsequent decreases in pH readings and electrical conductivity denoted increasing acidity and complexation with materials such as minerals. TSS readings increased at the same time, which corresponded to moisture uptake. Additionally, despite certain samples being over-fortified in vitamin C to countermeasure an expected nutrient degradation, the concentration of vitamin C decreased consistently across the samples. The findings summarize that storage of powdered infant formula after opening at room-temperature affects powdered infant formula in various aspects affecting physical, chemical, and nutritional safety over overtime.